EPC Agenda 2004-04-01 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda - Approved. Minutes of 3/3/22 - Approved. President Report. Provost Report. Consent: From EPC: GEP Minor - Approved. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Student Representative Report. Resolution on United in Kindness - Second Reading - Approved unanimously. EPC Report. FSAC Report. SAC Report. CFA Report. Good of the Order.